Willingness to Pay for Mortality Risk Reduction and Environmental Kuznets Curve Hypothesis - Masafumi Morisugi; Hiroshi Sao; Eiji Ohno (European Regional Science Association (ERSA), 2013)
Global Warming will cause severe decline of water quality over the world in near future, and mortality risk due to water pollution causing diseases of diarrhea or digestive organs has been one of serious problems especially for Asian developing countries. Generally speaking, implementation of sewage and water-supply system might be the most effective policy against such health problems. By the way, the timing to carry out a policy or project against such a problem is typical and central debate of Environmental Kuznets Curve hypothesis. It suggests that there exists an empirical relation between per capita income and some measures of environmental quality, and that as income goes up there is increasing environmental degradation up to a point, after which environmental quality improves. The relation has an 'inverted-U' shape. However, only a limited water pollution matters seems to obey to the rule, and several recent empirical findings are mostly consistent with negative remarks about the law. Our main objective is to examine effectiveness of EKC hypothesis with survey data sets in Laos and Vietnam to ask citizens' WTP (Willingness to Pay) for mortality risk reduction as a contingent policy or project has been implemented. The WTP can be also estimated for each category of participant's generation, as 20's, 30's, 40's, 50's, and over 60. On this procedure, we found also relative robust and characteristic relationships between their age or income and WTP. In a subsequent theoretical study, we found that these relationships holds theoretical consistency for both of Option Price Model and Optimal Expenditure Decision Model, those are discriminated by typical ways of answering questions of the participants and assumed that the one doesn't interest in the world after his death. 6 propositions are also derived in this procedure, and some of them refer to functional form of WTP with respect to a variable of risk reduction. So far as our empirical findings are consistent with theoretical suggestions, EKC hypothesis is supported well at least about transition of their preference for improved environment with economic development, and the turning point of EKC does not rely only on the income level but also aging degree of the society.
Keywords: I15; Q51; H43; 330; mortality risk; Environmental Kuznets Curve; option price; optimal expenditure